2011
DOI: 10.1097/ta.0b013e318222f380
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Enhanced Mobilization of Bone Marrow Derived Cells to Site of Injury

Abstract: Local SDF-1 and/or systemic G-CSF can effectively increase BMDC homing to sites of traumatic injury in an additive way and improve wound healing. This process appears to be mediated predominantly through MSC. Additional investigations are needed to identify the optimal adjuncts to improve wound healing following severe traumatic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
70
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 28 publications
1
70
0
Order By: Relevance
“…Lastly, we did not perform an analysis of the mobilization effect of subcutaneous G-CSF administration or a phenotypic study of the cells that were recruited to the surgical site. The effect of G-CSF administration on stem cell mobilization is well established in murine and other models [11,22,28,35,37,46].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lastly, we did not perform an analysis of the mobilization effect of subcutaneous G-CSF administration or a phenotypic study of the cells that were recruited to the surgical site. The effect of G-CSF administration on stem cell mobilization is well established in murine and other models [11,22,28,35,37,46].…”
Section: Discussionmentioning
confidence: 99%
“…staining was performed to identify the infiltrating cells, previous studies using stem cell mobilization agents in the setting of cerebrovascular ischemia [41], acute myocardial infarction [35], and lung contusion [22] demonstrated similar increases in cellularity and have determined that cells mobilized from marrow cavities indeed transmigrate into injured tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Controversy exists as to the physiological role of these cells under native in vivo conditions; however, it has been suggested that MSCs may be perivascular cells (''pericytes'') that support vascular homeostasis and tissue repair. In preclinical studies, perivascular MSCs appear to be mobilized into the circulation under inflammatory conditions, such as traumatic lung injury 5 or hypoxia. 6 A similar mobilization of MSCs into the circulation has also been observed clinically in elderly patients following traumatic hip fracture.…”
mentioning
confidence: 99%